Endoscopic Corneal Neurotization: Cadaver Feasibility Study. Issue 3 (May 2018) - Leyngold, Ilya; Weller, Christopher; Leyngold, Mark; Espana, Edgar; Black, Kaelan D.; Hall, Kathryn L.; Tabor, Mark
Abstract : Purpose: The authors describe a cadaver feasibility study investigating a minimally invasive technique for corneal neurotization with the supraorbital nerve harvested endoscopically. Methods: A cadaver study was performed to investigate the technical feasibility of corneal neurotization via endoscopic supraorbital nerve transfer to the corneoscleral limbus. Results: Endoscopic corneal neurotization was successfully performed on each cadaveric hemiface. Conclusion: The use of an endoscope allows for a minimally invasive approach to corneal neurotization with the supraorbital nerve. Abstract : The following investigation represents a cadaveric feasibility study supporting the use of a minimally invasive endoscopic approach to supraorbital nerve transfer and corneal neurotization in the setting of neurotrophic keratopathy.